PENGARUH UNDANG-UNDANG CIPTA KERJA NO. 6 TAHUN 2023 TERHADAP PENGELOLAAN FLY ASH DAN BOTTOM ASH (STUDI PADA PLTU AMURANG) - Denny Omega Tereima, Devry; Novy Tuwaidan, Arthur; Jehezkiel Lanawaang, Janeman (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
The enactment of the Law No. 6 of 2023 has brought significant changes to the management of Fly Ash and Bottom Ash (FABA), including the reclassification of FABA as non-hazardous and non-toxic waste (non-B3 waste) and the extension of the storage period in the Ash Disposal Area from 365 days to 3 years. This study aims to analyze the impact of Law No. 6 of 2023 on the management of Fly Ash and Bottom Ash at the Amurang Coal-Fired Power Plant (PLTU Amurang). Using a normative legal research method, the findings provide comprehensive insights into the effects of implementing Law No. 6 of 2023 on FABA waste management. These findings are expected to contribute to the development of more effective and sustainable environmental policies, as well as offer practical recommendations for power plant operators to improve environmentally friendly and economically valuable waste management practices.